(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2021)
The current study was conducted in the water ecosystem of Lake Hajjar - southern Libya, where this artificial lake was designed in the mid-1980s for the purpose of using it as an oxidation lake and a filtering of wastewater treated in the first stage of Sebha, as a kind of water rationing in desert areas. The lake has an area of 25 hectares and depths between 1-5 meters. With the aim of identifying the current environmental situation by studying the overall physiochemical properties of the water, the results showed that the lake water tends to be neutral (6.29 - 7.38), low in salinity (2.27 - 2.51 dS / m) and with relatively low concentrations of phosphorus (mg/L 4.87 - 5.63) and nitrogen (mg/L 4.54-6.41). It is also evident that the ecosystem has reached the stage of the reed-swamp stage as an advanced stage of the ecological succession in which the stalk plant, which has a high competitiveness under the environmental conditions of the medium, is prevalent and is characterized by its pox system strongly installed in the sediment layer around the lake and the presence of rhizome stems that help in the process. The different sedimentation and thus caused the decrease of the lake depth and the appearance of its bottom and partial exposure to the atmosphere.